Bitter and sweet - Feder, Sandra V. (Groundwood Books, House of Anansi Press, 2018)
Despite her grandmother's wise words about how moving to a new place can be both bitter and sweet, Hannah feels only bitterness as she tries to get used to her new house. But when she sees the new home in the soft light of the Shabbat candles and a new friend reaches out with a special gift, Hannah begins to realize that sweetness can come from unexpected places. Includes author's note about Jewish traditions.